An overview of Circular Economy in Portuguese SMEs of Ornamental Stone sector: how the current challenges shape the plans for the Future - Duarte de Almeida, I.; da Silva, Agostinho; Kaupp, M. (29th EurOMA Conference - Brilliance in resilience: operations and supply chain management’s role in achieving a sustainable future, 2022)
A Circular Economy (CE) theoretical Business model for the Portuguese Ornamental Stone sector (POSs) is presented. The qualitative analysis applied to SMEs from POSs reveals drivers and hampers whose equilibrium constitutes current challenges in shaping the CE in these SMEs. The existence result for a CE optimum integration in the POSs, minimizing resources depletion, raw material losses, and implementation costs are explicitly proved. Effects of combining enablers found for SMEs in the transition towards CE are illustrated. The cost-effectiveness perception analysis is carried out to reveal cost-effective strategy plans that could be implemented to increase the circularity of POSs in the future.